The role of beachrock formations in the evolution of embayed coastal zones of Attica (Greece) in relation to sea level rise. The case of Kalivia beach zone. - Koutsomichou, I.; Poulos, S.; Evelpidou, N.; Anagnostou, Ch.; Ghionis, G.; Vassilopoulos, A. (Geografia Fisica e Dinamica Quaternaria, 2009)
The coastline of Attica incorporates a great number of pocket beaches, which are characterised further by the presence of extensive beachrock formations. The present study concerns the evolution (past, present and future) of the Kalyvia beach zone, located at the western coast of Attica and at a distance of 42 km from the city of Athens. The subaerial part of the beach zone consists of mixed materials (mainly sand, granules and gravel), while extensive beachrock formations exist on its shoreface. The beach is exposed primarily to southern wind-induced waves, the largest of which (offshore wave height up to 6m and period >11sec) begin to break at about 8 m of water depth and have a run-up capability of approximately 1.5 m. Most of the subaqueous part of the Kalyvia beach zone is lithified, as the beachrocks extend from the shoreline down to >8 m of water depth. This part of the beach zone may be subdivided further into three units: the deeper one (water depths >7m), the middle (depths 5-6.5 m) and the upper unit (from 4 m depth up to the shoreline). This almost continuous presence is related to the gradual sea level rise during the upper Holocene (past 6.000 years), indicating also a relative climatic stability and/or homogeneity during this period, although some morphological and structural differences in the beachrock indicate changes either in the rate of sea level rise or in the prevailing climatic conditions. Over the last decades, human activities and constructions have deprived the beach of hinterland sediment supply, changing, therefore, its sedimentological character. During this period, beachrocks have played a ‘protective role’ stabilizing and reducing substantially the retreat of the beach zone, which on the basis of the landward boundary displacement of the beachrocks has been estimated to be in the order of 30cm per year from 1969 to 2005. This retreat is attributed to the marine erosion of the sediment that used to cover the upper beachrock formations, in combination to the sea-level rise (approx. 18 cm over the past century) and the lack of sediment supply. Moreover, this degradation of the Kalyvia beach zone is expected to be intensified by the potential future sea level rise (approximately 38 cm for the year 2100).